2003
DOI: 10.1104/pp.103.020453
|View full text |Cite
|
Sign up to set email alerts
|

β-Alanine N-Methyltransferase of Limonium latifolium. cDNA Cloning and Functional Expression of a Novel N-Methyltransferase Implicated in the Synthesis of the Osmoprotectant β-Alanine Betaine

Abstract: ␤-alanine (Ala) betaine, an osmoprotectant suitable under saline and hypoxic environments, is found in most members of the halophytic plant family Plumbaginaceae. In Limonium latifolium (Plumbaginaceae), it is synthesized via methylation of ␤-Ala by the action of a trifunctional S-adenosyl l-methionine (Ado-Met): ␤-Ala N-methyltransferase (NMTase). Peptide sequences from purified ␤-Ala NMTase were used to design primers for reverse transcriptase-PCR, and several cDNA clones were isolated. The 5Ј end of the cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…This was not surprising as both genes share 61% overall identity and are even more homologous (71%) comparing only the 750 bp initial PCR fragment. Very low identity rates are found, if amino acid sequence comparison is expanded to other plant N-methyltransferases from alkaloid metabolism (Table 1b), such as coclaurine-N-methyltransferase from Coptis japonica (Choi et al 2002) and xanthine-N-methyltransferases from Coffea arabica (Uefuji et al 2003) or to the stress metabolite forming b-alanine-N-methyltransferase from Limonium latifolium (Raman and Rathinasabapathi 2003). SAM-dependent methyltransferases often share little sequence identity Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This was not surprising as both genes share 61% overall identity and are even more homologous (71%) comparing only the 750 bp initial PCR fragment. Very low identity rates are found, if amino acid sequence comparison is expanded to other plant N-methyltransferases from alkaloid metabolism (Table 1b), such as coclaurine-N-methyltransferase from Coptis japonica (Choi et al 2002) and xanthine-N-methyltransferases from Coffea arabica (Uefuji et al 2003) or to the stress metabolite forming b-alanine-N-methyltransferase from Limonium latifolium (Raman and Rathinasabapathi 2003). SAM-dependent methyltransferases often share little sequence identity Fig.…”
Section: Discussionmentioning
confidence: 96%
“…al., 2003), Limonium latifolium (Rathinasabapathi et. al., 2001;Raman and Rathinasabapathi, 2003), Mesembryanthemum crystallinum (Vera-Esterella et. al., 2004), Atriplex hortensis (Shen et.…”
Section: Wild Species To Understand Specific Stress Adaptationsmentioning
confidence: 98%
“…al., 2001). A full length cDNA for beta-alanine N-methyltransferase from L. latifolium was cloned and characterized recently (Raman and Rathinasabapathi, 2003). Experiments in our laboratory showed that in a variety of plant species, pantothenate synthesis was limited by d-pantoate and not by beta-alanine (Rathinasabapathi and Raman, 2005).…”
Section: Beta-alanine and Beta-alanine Betainementioning
confidence: 99%
See 1 more Smart Citation
“…Further, GB has been shown to play an essential role in maintaining the health of vital organs, such as the liver, heart and kidneys in humans (Craig 2004;Likes et al 2007). GB reduces cardiovascular risk factors and betaine and choline decrease the risk of infant neural tube defects (Raman & Rathinasabapathi 2003).…”
Section: Introductionmentioning
confidence: 99%